Hangry in the field: An experience sampling study on the impact of hunger on anger, irritability, and affect - Swami, Viren; Hochstöger, Samantha; Kargl, Erik; Stieger, Stefan (PLOS ONE, 2022)
The colloquial term “hangry” refers to the notion that people become angry when hungry, but very little research has directly determined the extent to which the relationship between hunger and negative emotions is robust. Here, we examined associations between everyday experiences of hunger and negative emotions using an experience sampling method. Sixty-four participants from Central Europe completed a 21-day experience sampling phase in which they reported their hunger, anger, irritability, pleasure, and arousal at five time-points each day (total = 9,142 responses). Results indicated that greater levels of self-reported hunger were associated with greater feelings of anger and irritability, and with lower pleasure. These findings remained significant after accounting for participant sex, age, body mass index, dietary behaviours, and trait anger. In contrast, associations with arousal were not significant. These results provide evidence that everyday levels of hunger are associated with negative emotionality and supports the notion of being “hangry”.